Detailed evaluation of Mobius3D dose calculation accuracy for volumetric-modulated arc therapy. (June 2020) - Kim, Jihun; Han, Min Cheol; Lee, Eungman; Park, Kwangwoo; Chang, Kyung Hwan; Kim, Dong Wook; Kim, Jin Sung; Hong, Chae-Seon
Highlights: Mobius3D has uncertainties in calculating fluence maps due to inaccurate consideration of MLC tongue-and-groove effect. Mobius3D underestimates doses for small fields. The aforementioned uncertainties in Mobius3D can affect VMAT patient-specific QA results. Given Mobius3D's dose calculation uncertainties, dosimetric leaf gap optimization should be carefully performed. Abstract: Purpose: To perform a detailed evaluation of dose calculation accuracy and clinical feasibility of Mobius3D. Of particular importance, multileaf collimator (MLC) modeling accuracy in the Mobius3D dose calculation algorithm was investigated. Methods: Mobius3D was fully commissioned by following the vendor-suggested procedures, including dosimetric leaf gap (DLG) optimization. The DLG optimization determined an optimal DLG correction factor which minimized the average difference between calculated and measured doses for 13 patient volumetric-modulated arc therapy (VMAT) plans. Two sets of step-and-shoot plans were created to examine MLC and off-axis open fields modeling accuracy of the Mobius3D dose calculation algorithm: MLC test set and off-axis open field test set. The test plans were delivered to MapCHECK for the MLC tests and an ionization chamber for the off-axis open field test, and these measured doses were compared to Mobius3D-calculated doses. Results: The mean difference between the calculated and measured doses across the 13 VMAT plans was 0.6% with an optimal DLG correction factor of 1.0. The mean percentage of pixels passing gamma from a 3%/1 mm gamma analysis for the MLC test set was 43.5% across the MLC tests. For the off-axis open field tests, the Mobius3D-calculated dose for 1.5 cm square field was −4.6% lower than the chamber-measured dose. Conclusions: It was demonstrated that Mobius3D has dose calculation uncertainties for small fields and MLC tongue-and-groove design is not adequately taken into consideration in Mobius3D. Careful consideration of DLG correction factor, which affects the resulting dose distributions, is required when commissioning Mobius3D for patient-specific QA.